Individual and community-related factors interfering with health equity in advanced age - Bobrowicz-Campos, E. (Let's Talk About Ageing. Congresso Multidisciplinar sobre Envelhecimento, 2022)
Digital transformation can bring many benefits to people's lives. However, like any process of change, digital transformation requires a complex response to its demands, and in situations where this response is not successful, it can contribute to the replication or even exacerbation of existing offline inequalities. The case of health services is particularly sensitive. The use of digital technologies in health can improve integrated and person-centred healthcare, bringing health services closer to citizens. However, in the absence of equipment or knowledge/skills or motivation that enable the goal-oriented and efficient use of these technologies, the access to healthcare may become limited, with this situation having serious implications for the citizens’ quality of life, well-being and health status. The greatest disparities in embracing and adapting to digital progress are documented among older adults, with their origin being associated to multiple sociodemographic, socioeconomic, sociocultural and personal factors. In the MIRROR project I propose to look at these factors in an integrated perspective, supported by theories that describe the processes of constructing cultural and autobiographical narratives, and that explain the contribution of these narratives in guiding an individual’s thoughts, beliefs and behaviours. This novel conceptual approach will result in identifying social meanings and values associated to digital transformation and shared in society, and in determining the mediating role they can have in the adoption of digital technologies by older adults and in their digital engagement, especially with regard to the use of health services in digital space. Based on the knowledge generated, health-related digital education program for use in older adults will be conceptualized, with the process being additionally supported by participatory research actions involving older adults and stakeholders from different sectors. It is expected that the MIRROR project will contribute to overcoming the existing barriers in relation to the participation of older adults in the digital transformation, increasing these citizens’ access to associated benefits. Among these benefits, close integrated and personalised healthcare should be highlighted, with its efficient monitoring of health status and the timely implementation of prevention and treatment approaches, both with relevant implications for reducing vulnerability to age-related health risks.